Risk factors for locally advanced cancer associated with ulcerative colitis: Results of a retrospective multicentric study in the era of biologics. Issue 1 (January 2020) - Rottoli, Matteo; Tanzanu, Marta; Di Candido, Francesca; Colombo, Francesco; Frontali, Alice; Chandrasinghe, Pramodh C.; Pellino, Gianluca; Frasson, Matteo; Warusavitarne, Janindra; Panis, Yves; Sampietro, Gianluca M.; Spinelli, Antonino; et al.
Abstract: Background: Patients affected by ulcerative colitis (UC) are more likely to develop colorectal cancer, and are often diagnosed with lymph node involvement (N+) at surgery. Aim: To identify the risk factors for N+ cancer in UC patients. Methods: Patients undergoing surgery from 2001 to 2018 in six European tertiary centres were included. N+ patients were compared to the control group (N−) for clinical variables. The evaluation of risk factors for N+ was assessed using univariate and multivariable logistic regression analyses. Results: A total of 130 patients were included. Median duration of disease was 21 years (1–52). Forty patients (30.8%) were N+ at surgery. Eighteen (13.8%) developed cancer within 10 years from the onset of UC. Younger age at surgery (Odds ratio -OR- 0.96, p = 0.042), left colon location (OR 2.44, p = 0.045) and the presence of stricture (OR 5.07, p = 0.002) were associated with N+. Conclusion: Location in the left colon, presence of strictures and younger age strongly correlated with a higher risk of N+ cancer, which could develop before the starting point of surveillance. Duration, extension and severity of disease were not associated with N+. These results should be considered in the evaluation of risk of advanced cancer in UC patients.